A Retrospective Analysis of the Trends in Acute Appendicitis During the COVID-19 Pandemic - Finkelstein, Paige; Picado, Omar; Muddasani, Kiranmayi; Wodnicki, Henry; Mesko, Thomas; Unger, Stephen; Bao, Philip; Jorge, Irving; Narayanan, Sumana; Ben-David, Kfir (Journal of laparoendoscopic & advanced surgical techniques. Part A, 2021)
The corona virus disease of 2019 (COVID-19) imposed new public health constraints that deterred people from coming to the hospital. The outcome of patients who developed appendicitis during mandated COVID-19 quarantine has yet to be examined. The main objective was to establish whether there was an increased rate of perforated appendicitis seen during COVID-19 quarantine. Secondary objectives included observing the type of procedure performed, length of stay, and associated complications. This retrospective analysis was designed to look at the rates of appendicitis and perforated appendicitis observed during mandatory "safer at home order" from March to May 2020. The same time period a year earlier was used for comparative analysis. The study utilized data gathered from a single health care system, which consisted of a large regional referral center with three emergency rooms (ERs). Patients were included in the study if they presented to any ER in our health care system with a chief complaint of acute appendicitis. Perforated appendicitis was determined either radiographically or intraoperatively. Interventions included surgery, percutaneous drainage, or medical management. There were 107 patients who were included. During quarantine, a total of 48 patients presented with acute appendicitis, with 16 perforations, compared with the previous year where 59 patients presented with acute appendicitis, with 10 perforations (33% versus 17% = .04). Most patients underwent laparoscopic appendectomy (91%, = 98), six patients (6%) were managed with intravenous antibiotics and 3 patients (3%) with percutaneous drainage. Patients who perforated had a longer duration of symptoms (2 versus 1, = .03), white blood cell count (13,190 versus 15,960 cells/mm , = .09), and longer operative time (72 versus 89 minutes, = .01). Patients who perforated had an increased length of stay and rate of complication. There was an overall increased rate of perforated appendicitis seen during quarantine compared with the previous year. Patients with perforated appendicitis had an increased length of stay, longer operative time, and increased rate of complications. Thus, although people were staying home due to public health safety orders, it negatively impacted those who developed appendicitis who may have presented to the hospital otherwise sooner.